Beyond conventional therapy: Synthesis of multifunctional nanoparticles for rheumatoid arthritis therapy - Ma Xinran (Nanotechnology Reviews)
Rheumatoid arthritis (RA) is a persistent inflammatory illness that causes joint destruction and dysfunction due to the activation of macrophages and the generation of reactive oxygen species. Current therapy choices frequently limit the effectiveness of targeting the inflammatory areas. To reduce inflammation and oxidative stress in RA, this research will create and assess multifunctional nanoparticles that selectively target inflammatory cells and deliver therapeutic medicines. Tannic acid, ferric chloride hexahydrate, methotrexate (MTX), and bovine serum albumin were conjugated using sonication and centrifugation to create the nanoparticles. Folic acid was added to improve the ability to target. Transmission electron microscopy, dynamic light scattering (DLS), UV-vis spectroscopy, and in vitro release experiments were used to characterize the nanoparticles. RAW 264.7 macrophage cells were used to test the cellular uptake of the nanoparticles using confocal microscopy and fluorescence-activated cell sorting (FACS). TFMBP-FA achieved 65.56%, and TFMBP reached 68.96%, indicating a high drug delivery rate for the synthesized nanoparticles. Confocal microscopy showed that the TFMBP-FA group had a greater density of fluorescent markers, indicating that the cells effectively targeted and absorbed the inflammatory environment. These results imply that the created nanoparticles may improve how medications are delivered during RA therapy.